Paying for the Piper: Capital and Labour in Britain's Offshore Oil Industry - McBride, Michelle (Labour / Le Travail, 1998)
The article reviews the book, "Paying for the Piper: Capital and Labour in Britain's Offshore Oil Industry," byCharles Woolfson, John Foster, and Matthias Beck.